SUP-Hesitant Fuzzy Interior Ideals in \(Γ\)-Semigroups - Khamrot, Pannawit; Gaketem, Thiti (Bulletin of the Section of Logic, 2024)
In this paper, we defined the concept \(\mathcal{SUP}\)-hesitant fuzzy interior ideals in \(Γ\)-semigroups, which is generalized of hesitant fuzzy interior ideals in \(Γ\)-semigroups. Additionally, we study fundamental properties of \(\mathcal{SUP}\)-hesitant fuzzy interior ideals in \(Γ\)-semigroups. Finally, we investigate characterized properties of those.